2012
DOI: 10.5923/j.ijaf.20120202.11
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Evaluation of Some Fungicides Alternatives Against <i>Fusarium Oxysporum</i> the Causal of Wilt Disease of Pepper (<i>Capsicum </i><i>a</i><i>nnum </i>L.)

Abstract: The inhibitory effect of the antagonistic bioagents, chemical plant resistance inducers and some essential oils against the linear growth of two isolates of F. oxysporum the wilt pathogen of pepper (Capsicum annum L.) was evaluated in vitro. The antagonistic microorganisms, Trichoderma harzianum, T. viride, T. aureiviride, Bacillus subtilis and Pseudomonas fluorescens were tested. Also, the tested chemical inducers were Sodium benzoate, Potassium bicarbonate, Potassium sorbate and Chitosan. Meanwhile, the test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…MB108 9 have obvious inhibitory effects on F. oxysporum . Bacillus subtilis and Pseudomonas fluorescens show superior inhibitory effects against F. oxysporum growth 10 . Moreover, many biocontrol agents regulate microbial community structures when applied to soil.…”
Section: Introductionmentioning
confidence: 99%
“…MB108 9 have obvious inhibitory effects on F. oxysporum . Bacillus subtilis and Pseudomonas fluorescens show superior inhibitory effects against F. oxysporum growth 10 . Moreover, many biocontrol agents regulate microbial community structures when applied to soil.…”
Section: Introductionmentioning
confidence: 99%
“…In India, occurrence of Fusarium wilt in bell pepper and chilli has been reported in various parts of country and causes up to 25 per cent losses (Madhukar & Naik, 2004). Naqvi (2004) reported 35 percent wilt incidence in many states of USA and it is also reported that after 30 days of soil infestation, Fusarium oxysporum kills 56% chilli seedlings (Mona et al, 2012). The yield loss due to the disease is known to vary from 10-80 percent worldwide (Loganathan et al, 2013).…”
Section: Geographical Distributionmentioning
confidence: 99%
“…In India, Fusarium wilt in chili has been reported in many regions and causes around 25% yield losses (Najar et al, 2006). In the USA (Roberts et al, 2004) recorded a 35% occurrence in various states, and it is also observed that after 30 days of soil infection, Fusarium oxysporum kills 56% of chili seedlings (Ragab et al, 2012). Globally, 10-80% yield reduction has been recorded due to this disease (Loganathan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to a survey, about 80% of Thailand's chili plant crop losses were attributable to fusarium wilt (Wongpia and Lomthaisong, 2010). In Egypt, Fusarium oxysporum destroyed 56% of chili seedlings after 30 days of its infestation in soil (Ragab et al, 2012). Moist soil and high temperatures play an important role in enhancing pathogen and disease development.…”
Section: Introductionmentioning
confidence: 99%